Look closer: The multidimensional patterns of post-stroke burden behind the modified Rankin Scale. Issue 4 (June 2021) - Rethnam, Venesha; Bernhardt, Julie; Johns, Hannah; Hayward, Kathryn S; Collier, Janice M; Ellery, Fiona; Gao, Lan; Moodie, Marj; Dewey, Helen; Donnan, Geoffrey A; Churilov, Leonid
Background: The utility-weighted modified Rankin Scale, representing patient perspectives of quality of life, is a newly proposed measure to improve the interpretability of the modified Rankin Scale. Despite obvious advantages, such weighting imperfectly reflects the multidimensional patterns of post-stroke burden. Aims: To investigate multidimensional patterns of post-stroke burden formed by individual domains of Assessment of Quality of Life and Barthel Index for each modified Rankin Scale category. Methods: In the A Very Early Rehabilitation Trial (n = 2104), modified Rankin Scale scores and modified Rankin Scale-stratified Barthel Index scores of Self-care and Mobility, and Assessment of Quality of Life scores of Independent Living, Senses, Mental Health and Relationships were collected at three months. The multivariate relationship between individual Assessment of Quality of Life and Barthel Index domains, and modified Rankin Scale was investigated using random effects linear regression models with respective interaction terms. Results: Of 2104 patients, simultaneously collected Assessment of Quality of Life, Barthel Index and modified Rankin Scale scores at three months were available in 1870 patients. While individual Assessment of Quality of Life and Barthel Index domain scores decreased significantly as modified Rankin Scale increased (p < 0.0001), the patterns of decrease differed by domains (p < 0.0001). Patients with modified Rankin Scale 0–1 had the largest post-stroke burden in the Mental Health and Relationship domains, while patients with modified Rankin Scale >3 showed the greatest burden in Independent Living, Mobility and Self-care domains. Conclusions: Across the modified Rankin Scale, individual domains are varyingly impacted demonstrating unique patterns of post-stroke burden, which facilitates appropriate assessment, articulation and interpretation of the modified Rankin Scale and utility-weighted modified Rankin Scale.